SEBUAH UJIAN PENEGAKAN HUKUM KEJAHATAN KESUSILAAN (Kasus Video Mesum) - -, Triwanto (Universitas Slamet Riyadi, 2010)
Abstrct : The purpose of law enforcement is often faced with the exam in its implementation, especially related regulations in it are still in debate and proving to be deepening as well as actors who have a high resistance Key words : Examination of law enforcement, Crime morality